Multi-objective Design Optimization of the Robot Grippers with SPEA2 - Avder, Ayşenur; Şahin, İsmail and Dörterler, Murat (International Journal of Intelligent Systems and Applications in Engineering, 2019)
Robot grippers are the tools used for gripping, moving and fixing objects. It is integrated into robotic systems that grippers can grip an object for at least one manoeuvre without any damage. Thus, the design optimization of robot grippers has been a research topic in resent. Robot grippers were optimized by various methods for different aims in previous studies. In this study, it is aimed a balanced gripping by optimizing the fluctuation of the power applied to an object by the grippers and power transfer rate between actuator and ends of a gripper. Strength Pareto evolutionary algorithm II (SPEA-II), a multi-objective optimization method, has been applied to the problem for this aim firstly. The experimental results were compared to the result of the previous studies. SPEA-II is superior to the competitor as the comparison.